2012
DOI: 10.2320/matertrans.e-m2012810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Amount of Vacancies on the Thermoelectric Properties of Cu–Ga–Te Ternary Compounds

Abstract: The CuGaTe ternary compounds: Cu 3 Ga 5 Te 9 , Cu 2 Ga 4 Te 7 , CuGa 3 Te 5 , CuGa 5 Te 8 , and CuGaTe 2 have zinc-blende or chalcopyrite structure. The compounds except for CuGaTe 2 contain vacancies in the cation site due to the valence mismatch between cation and anion, and the vacancy concentration is different between these compounds. Here we investigated the effect of the amount of vacancies on the thermoelectric (TE) properties of the CuGaTe ternary compounds. At room temperature, the presence of vacanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 13 publications
1
31
1
Order By: Relevance
“…At x=0.2, trace impurity phase Sb2Te3 (PDF: )is identified, indicating that the solubility of Sb in CGT is less than 0.2. . 16 It is interesting that both the a and c values show a decreasing tendency with Sb content increasing in the range of x≤0.05, and then remain relatively constant. Such a non-linear relation seems that the element Sb is not completely incorporated into the CTGT crystal lattice.…”
Section: Methodsmentioning
confidence: 91%
See 4 more Smart Citations
“…At x=0.2, trace impurity phase Sb2Te3 (PDF: )is identified, indicating that the solubility of Sb in CGT is less than 0.2. . 16 It is interesting that both the a and c values show a decreasing tendency with Sb content increasing in the range of x≤0.05, and then remain relatively constant. Such a non-linear relation seems that the element Sb is not completely incorporated into the CTGT crystal lattice.…”
Section: Methodsmentioning
confidence: 91%
“…It is observed that the sample at x=0.05 gives the highest ZT value (0.58 at 723 K), which is about two times that of the intrinsic CTGT, and 0.35 higher than the reported value 0.23. 16 This result indicates that the solid solution formation via the mixed Sb occupations is an effective approach to optimize the TE performance. The abnormal variation of the Hall carrier concentration with Sb content might be related to the structural modification.…”
Section: Transport Properties and Te Performancementioning
confidence: 95%
See 3 more Smart Citations